STREPTOCOCCUS MUTANS COUNT PROFILE ON FAMILY - Gutiérre llave, Margot (2004)
Dental caries is a mllltifactor infecting and contagious disease. Its formation and development are conditioned to people's life style. Streptococus mutans is a microorganism , which has a leading position in dental caries. Its qllantification on saliva is a cariogenic risk indicator. Family harbor a conjunct of positive and negative forces that influence each member behavior making it to function in good or bad mood. In past studies, it was demonstrated that it is possible to transmit eolonies of S. mutans trough contaminated utensils with saliva like those used in familiar environment . In this pre sent study, it was determined if members of the same family show a similar eount of S mutans trough Matsukubo m'ethod. For this objeetive, 10 families were selected; with 4 or 5 members eaeh one, eonformed by parents and ehildrenfrom 3 to 20 years old. Results show that 90% of families showed a similar eount of S. mutans within an equal range in very one of the family members.